The evaluation of research papers in the XXI century. The Open Peer Discussion system of the World Economics Association - Ietto-Gillies, Grazia (Frontiers in Computational Neuroscience, 2012)
The paper starts with a brief discussion of the traditional peer review system of research evaluation, its role and the criticisms levelled at it. An analysis of specific problems in economics leads to a full discussion of the Open Peer Review (OPR) system developed by the World Economics Association (WEA) and the principles behind it. The system is open in the following two respects: (a) disclosure of names of authors and reviewers; and (b) inclusivity of potential reviewers in terms of paradigmatic approaches, country and community. The paper then discusses the applicability of the same system to other disciplines. In doing so it stressed the aims of various evaluation systems and the possible pitfalls of rating systems. It also speculates on the future of journal publication.